Requalificação urbana no bairro do Educandos: uma proposta para habitação de interesse social e parque urbano - Siqueira, Talita da Silva (Brasil, 2022)
The present project has as its theme Urban Requalification in the Neighborhood of Educandos: A Proposal for Social Housing and Urban Park. Knowing that the development of social housing in Brazil has presented over the years a discontinuity of actions between governments, promoting the maintenance of conflicts between modernization, exclusion and inequality, focusing mainly on numbers and not efficiency and/or quality, the main objective is to design units that address the issues of dimensionality, functionality and flexibility, in which, focused on housing, aims at design quality thought from the scope of the city to the project itself. With this, the question of the social role of architecture, turns to the possibility of transforming not only the physical space - housing, but also the actions that are externalized in it, the presence of life, culture, and diversity that is inserted in it, aiming at the presentation of proposals that aim at a quality architecture for the most differentiated segments of the city, conceiving spaces that seek connectivity between the intervention area and its surroundings. Thus, this project seeks, within the proposed theoretical-methodological framework, to meet the objectives presented, proposing the insertion of a Social Interest Housing project for the community of the Educandos neighborhood, through access to quality housing together with the proposal for improvement surroundings, through the creation of an urban park.